Perancangan Aplikasi Website untuk Sistem Informasi Rekam Medis di Klinik K-24 Merpati - Sartika Lina Mulani Sitio; Darmawati (Riau Jurnal Teknik Informatika, 2025)
K-24 Merpati Clinic is one of the health service facilities that handles various patient needs, including recording and managing medical record data. However, the recording process that is still carried out manually causes various problems such as delays in searching for patient data, the risk of losing archives, and inefficiencies in the management of medical information. This problem has an impact on the quality of services and the speed of medical decision-making by health workers. As a solution, a website application was designed for a medical record information system that can be accessed in an integrated and real-time manner. This application aims to assist medical and administrative staff in managing patient data digitally, from registration, diagnosis, to medical history. The method used in the development of this system is the Waterfall model, which was chosen because it has a systematic workflow and is appropriate for projects with clearly defined needs from the outset. The result of this study is a website application that has been tested using the black box testing method and shows that all functions run well according to user needs. This system is able to improve work efficiency, speed up patient data search, and minimize the risk of information loss. With the implementation of this information system, K-24 Merpati Clinic can provide faster, more precise, and digitally organized health services.